2017
DOI: 10.1108/k-03-2016-0038
|View full text |Cite
|
Sign up to set email alerts
|

Consumer attitudes toward online video advertisement: YouTube as a platform

Abstract: Purpose Online video advertisement is a wide-ranging phenomenon on the internet that provides huge opportunities for business enterprises. The revenues of website service providers come primarily from advertisement. However, it is rare to find research focusing on consumer attitudes toward online video advertisement. This study aims to investigate consumer attitudes toward advertisement while they are watching online videos on YouTube. Design/methodology/approach The paper followed Brackett and Carr’s (2001)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
120
2
16

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(154 citation statements)
references
References 33 publications
16
120
2
16
Order By: Relevance
“…Hence, products and brands should continue to use YMC such as promotions, advertising, celebrity endorsers, testimonials, influencers, and product placement in bid to create awareness among Gen Y, which have a positive influence on the cognitive attitudinal relationship and will ultimately have an impact on the final purchase decision (due to the hierarchical nature of consumer responses). Dehghani et al (), Chungviwatanant et al (), Mansour (), Zhang and Mao (), Yang et al (), Viertola (), and Vingilisa et al () assert that informativeness (knowledge) has a positive influence on consumer attitudes and behavior as a result of various forms of YMC; hence, organizations should ensure that they continually provide enlightening, engaging, instructive, entertaining and trustworthy content on the OVIS. A number of marketers use YouTubers (celebrity endorsers), testimonials, and influencers to provide information and recommend the organizations products and brands, in a bid to influence the different hierarchical attitude phases and eventually purchase, which is principally directed at the younger generations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, products and brands should continue to use YMC such as promotions, advertising, celebrity endorsers, testimonials, influencers, and product placement in bid to create awareness among Gen Y, which have a positive influence on the cognitive attitudinal relationship and will ultimately have an impact on the final purchase decision (due to the hierarchical nature of consumer responses). Dehghani et al (), Chungviwatanant et al (), Mansour (), Zhang and Mao (), Yang et al (), Viertola (), and Vingilisa et al () assert that informativeness (knowledge) has a positive influence on consumer attitudes and behavior as a result of various forms of YMC; hence, organizations should ensure that they continually provide enlightening, engaging, instructive, entertaining and trustworthy content on the OVIS. A number of marketers use YouTubers (celebrity endorsers), testimonials, and influencers to provide information and recommend the organizations products and brands, in a bid to influence the different hierarchical attitude phases and eventually purchase, which is principally directed at the younger generations.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, RO has the fourth fastest Internet speed across the globe; this is in comparison with SA's ICT poor Internet connection speed and inferior ICT infrastructure, which has begun to fall behind a number of other African developing countries (Duh & Struwig, 2015;Lesame, 2013;Petzer & De Meyer, 2013;Speedtest, 2019;Stokes, 2017). As discussed in prior text, Chungviwatanant et al (2016), Dehghani et al (2016), Mansour (2016), Zhang and Mao (2016), Yang et al (2017), and Zaitceva (2018) reported that informativeness had a positive influence on various attitudes due to several different YMC types. This study established that a positive relationship exists between awareness and knowledge as a result of YMC among Gen Y, and therefore has contributed to the attitude-to-advertising and cohort analysis theoretical frameworks.…”
Section: H8: Advertisement Viewership Numbers-awareness → Knowledgementioning
confidence: 92%
See 1 more Smart Citation
“…behind in the possibilities of communication with real and potential consumers. In the works of Russian and foreign researchers, advertising integrations in video blogs are considered as a highly effective kind of guerrilla marketing [8][9][10][11][12][13], oriented mostly to a young consumer audience [14,15].…”
Section: Problem Statementmentioning
confidence: 99%
“…Compelling financial literacy is a decisive factor, of which; farmers can proactively determine availability and accessibility to financial services [4]. For example, when young adults (ages [18][19][20][21][22][23][24] in the United States of America were asked the high-school level course that most benefited their lives, more than 50% responded in favor of "money management". Georgia, Idaho, and Texas mandated financial education; after three years of implemention, all the three observed increment in credit scores and lower delinquency rates within credit accounts [5].…”
Section: Introductionmentioning
confidence: 99%